Frequency of Stent Thrombosis in Patients with Acute Coronary Syndrome - Khan, Tashfeen Irtaza; Khan, Owais; Hussain, Cheragh (Indus Journal of Bioscience Research, 2025)
Background: Stent thrombosis is very common in individuals following percutaneous coronary intervention. Objective: The aim of this study was to find out the Frequency of stent thrombosis in patients with acute coronary syndrome. Material and method: The current cross-sectional study was carried out at the Department of Cardiology in Hayatabad Medical Complex, Peshawar from 1st February 2025 to 1st June 2025 after taking approval from the research committee of the hospital. The WHO sample size calculator was used to determine the sample size. 120 patients constitute the study's estimated sample size. Consecutive Non-Probability Sampling method was used. Individuals of both gender and different age groups (ranged 18-80) years diagnosed with acute coronary syndrome who underwent PCI with stent placement at Hayatabad Medical Complex were included. A structured questionnaire and a review of the patients' medical records were used to collect the data. Version 20.0 of the SPSS program was used to analyze the data. The mean as well as the standard deviation (SD) was used to summarize continuous variables, such as age, vascular size, and the total number of stents implanted. Important independent factors including age, gender, and stent features (such as stent type and bifurcation lesions) was applied to stratify stent thrombosis. Following stratification, correlations between categorical variables (such as the incidence of stent thrombosis & risk factors including diabetes and hypertension) was evaluated using the chi-square test. The p value < 0.5 was statically significant. Results: A total of 120 patients diagnosed with acute coronary syndrome who underwent PCI with stent placement were enrolled. The mean age of the study participants was 45.76±9.11 years.  Stent thrombosis was seen 12 (10%) individuals. The death rate among sub-acute thrombosis participants within thirty days of the first PCI was found to be 1 (8.3%). Within thirty days following the procedure, the rate of re-admission was three (25%), the rate of re-infarction was five (41.6%), and the rate of re-intervention was 25%. Diabetes mellitus is linked to increased incidence of sub-acute stent thrombosis among the individual variables (p=0.04). Among the lesion-related characteristics, patients with sub-acute stent thrombosis had substantially higher rates of smaller vessels and bifurcation lesions (p-values of 0.002 and 0.05, respectively). The under sizing of the stent (p